2015
DOI: 10.1097/rlu.0000000000000870
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Prostate Carcinoma Presenting as a Superscan on 68Ga-PSMA PET/CT

Abstract: Abstract:We describe the finding of a metastatic superscan detected by 68 Ga-PSMA PET/CT imaging. A 63-year-old man with metastatic prostate carcinoma underwent 68 Ga-PSMA PET/CT imaging for staging and evaluation of the most appropriate therapeutic option. Images demonstrated diffuse and extensive skeletal uptake in the axial and appendicular skeleton, corresponding to the typical red marrow distribution. Intense soft tissue uptake was also seen in the prostate and multiple pelvic and abdominal lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…After the full texts of potentially eligible studies were read, 45 papers were included. An overview of the 37 included papers is shown in Table 1 (31 case series) and Table 2, in which six single cases are presented (Chakraborty et al, 2015b;Lawal et al, 2015;Uprimny et al, 2015;Agarwal et al, 2016;Sasikumar et al, 2016;Soydal et al, 2016). Finally, one radiochemistry study was excluded because it reported data from a single patient using 68 Ga-PSMA-11 versus 68 Ga-CHX-A"-DPTA-PSMA PET/CT, an uncommon PET ligand (Wustemann et al, 2016).…”
Section: Characteristics Of the Included Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…After the full texts of potentially eligible studies were read, 45 papers were included. An overview of the 37 included papers is shown in Table 1 (31 case series) and Table 2, in which six single cases are presented (Chakraborty et al, 2015b;Lawal et al, 2015;Uprimny et al, 2015;Agarwal et al, 2016;Sasikumar et al, 2016;Soydal et al, 2016). Finally, one radiochemistry study was excluded because it reported data from a single patient using 68 Ga-PSMA-11 versus 68 Ga-CHX-A"-DPTA-PSMA PET/CT, an uncommon PET ligand (Wustemann et al, 2016).…”
Section: Characteristics Of the Included Papersmentioning
confidence: 99%
“…Finally, one radiochemistry study was excluded because it reported data from a single patient using 68 Ga-PSMA-11 versus 68 Ga-CHX-A"-DPTA-PSMA PET/CT, an uncommon PET ligand (Wustemann et al, 2016). An overview of the 37 included papers is shown in Table 1 (31 case series) and Table 2, in which six single cases are presented (Chakraborty et al, 2015b;Lawal et al, 2015;Uprimny et al, 2015;Agarwal et al, 2016;Sasikumar et al, 2016;Soydal et al, 2016). Most of the studies included patients with biochemical recurrence, but some studies included data on staging, whereas, other studies used populations with different stages of prostate cancer.…”
Section: Characteristics Of the Included Papersmentioning
confidence: 99%
“…Superscan-like images have also been shown with other tracers as 18 F-fluoride 7 and more recently with 68 Ga-PSMA. 8 …”
Section: Figurementioning
confidence: 97%
“…Prostate specific membrane antigen (PSMA) is a trans‐membrane glycoprotein that is overexpressed on prostate cancer cells . Its level of expression increases with increasing tumor aggressiveness . Gallium‐68 (Ga‐68) is obtained from a long‐lived Germanium‐68/Gallium‐68 generator (Ge‐68/Ga‐68 generator) and provides about 6 month supply of Ga‐68.…”
Section: Introductionmentioning
confidence: 99%
“…8 Its level of expression increases with increasing tumor aggressiveness. 9 Gallium-68 (Ga-68) is obtained from a long-lived Germanium-68/Gallium-68 generator (Ge-68/Ga-68 generator) and provides about 6 month supply of Ga-68. Ga-68 PSMA is labeled in-house in the nuclear medicine laboratory hence a reliable supply of the radiopharmaceutical is ensured.…”
Section: Introductionmentioning
confidence: 99%